LO38: Assessment of pain and provision of non-pharmacologic analgesia to children by prehospital providers in Southwestern Ontario: a cross-sectional study. (May 2019) - Teefy, J.; Mustafa, H.; Poonai, N.; VanAarsen, K.; Dukelow, A.
Abstract : Introduction : There is abundant evidence that in children, assessment and pharmacologic treatment of pain by prehospital providers is suboptimal. Most paediatric calls are performed by primary care paramedics who are unable to administer pharmacologic analgesia to children but can administer non-pharmacologic therapies. We sought to describe the proportion of children provided non-pharmacologic analgesia by prehospital providers.Methods : We reviewed all ambulance call reports (ACR) of children age 0-17 years with an acutely painful condition (headache, abdominal pain, possible fracture, head/ears/eyes/nose/throat pain, back pain, and unclassified pain) who were transported to the Children's Hospital, London Health Sciences Centre between 2008 and 2017. We excluded ACRs lacking data pertaining to the primary outcome. Data collection was recorded by two blinded assessors using a study-specific ExcelTM sheet. The primary outcome was the proportion of children offered non-pharmacologic analgesia. We performed a hierarchical stepwise logistic regression on the primary outcome using covariates defined a priori: age, sex, visible deformity, documentation of pain score, and complaint.Results : Of 19782 ACRS, we report the preliminary results of 500 ACRs reviewed from Jan 1 to Feb 22, 2016. Of the 403 ACRs eligible for analysis, the median (IQR) age was 13 (8) years and 174 (43.2%) were females. 309/403 (76.7%) calls involved primary (as opposed to advanced) care paramedics. Pain assessments were performed in 171/403 (42.4%) calls, most commonly the 0-10 verbal numeric rating scale [128/171 (74.8%)] and the median (IQR) score was 7 (4) (n = 128). Non-pharmacologic analgesia was offered in 72/403 (17.9%) of calls, most commonly ice (37/72, 51%) and splint (29/72, 40%). In the multivariate model, significant predictors of non-pharmacologic analgesia included older age (OR 1.1; 95% CI: 1.1, 1.2; p = 0.01) and visible deformity (OR 8.2; 95% CI: 2.5, 30.2; p = 0.001). Sex (p = 0.62), documentation of pain score (p = 0.81), and complaint (p = 0.05) were not significant predictors.Conclusion : In this preliminary analysis, the provision of non-pharmacologic analgesia to children in Southwestern Ontario by prehospital providers was suboptimal despite moderate to severe levels of pain. Less than half of patients had pain assessments documented. There is a clear need for education surrounding pain assessment and non-pharmacologic analgesic options in children among prehospital providers.